Finite element - Dual boundary element method for hydroelastic analysis of very large floating structures protected by perforated barrier. (15th January 2023) - Nguyen, H.P.; Liang, H.; Luong, V.H.
Abstract: This paper presents a Finite Element – Dual Boundary Element Method (FE-DBEM) for hydroelastic analysis of very large floating structures protected by vertical perforated barrier. The structure and barrier are modelled based on the shell theory, while the linear potential flow theory is employed for modelling wave structure interactions. The algebraic equations of the fluid-structure interaction are obtained by using the Finite Element Method (FEM) and Dual Boundary Element Method (DBEM). In DBEM, an approximation method is proposed for calculating the hypersingular integrals associated with the perforated barrier. The proposed method is validated by comparing with published experimental and mathematical results. As compared to the previously proposed Finite Element – Multi-Domain Boundary Element Method, the method presented in this paper has an advantage that the fluid domain does not need to be decomposed into sub-domains in the formulation. In addition, the same mesh of elements can be adopted in the DBEM and FEM; and thus, these methods can be coupled easily for fluid-structure-interaction analysis. Highlights: Finite Element – Dual Boundary Element Method is proposed. Numerical results are compared with available experimental/semi-analytical data. Hydroelastic analysis of very large floating structures protected by perforated barrier.